ADVERBIA DALAM BAHASA INDONESIA: TINJAUAN BENTUK DAN PERILAKU SEMANTISNYA - Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this study was (1) to describe the form of the adverb in Indonesian and (2) describe the semantic behavior. The research data in the form of sentences in which there is an adverb. Source of research data is a daily newspaper published Kedaulatan Rakyat September 2014. Methods of providing the data used are the method observation. Data analysis method used is the distributional method with basic techniques for segmenting immediate constituents and advanced substitution technique, permutation technique, and deletion technique. Presentation of the results of the analysis of data using informal methods. The results showed that (1) the adverbs in Indonesian can take the form of single and combined. Single adverb form of base word, affixed word, and reduplicated word, whereas the combined form of adverb-adverb and adverbial does not co-exist side by side; (2) In terms of semantic behavior of adverbs are qualitative adverbs, quantitative adverbs, limitedly adverbs, frequentative adverbs, temporal adverbs , contrastive adverbs, necessity adverbs, and desire adverb.